Modifikasi Gerobak Sampah sebagai Solusi Kebersihan - Theodura Bura; Alexandro Kaauni; Anjelia Boe; Nelcy Mite; Wens Nagul (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Due to the continuously increasing volume, the difficulty in distinguishing types of waste, and the heightened public awareness of environmental cleanliness, waste is the result of activities that are no longer used in the production process, so stakeholders must have the ability to manage waste effectively. One of the current problems is trash bins; the trash bins currently in use are only designed to transport waste materials without any other purpose.